ChemInform Abstract: ent‐Abietane Diterpenoids with anti‐Neuroinflammatory Activity from the Rare Chloranthaceae Plant Chloranthus oldhamii. Issue 40 (16th September 2016) - Xiong, Juan; Hong, Zhi‐Lai; Xu, Peng; Zou, Yike; Yu, Shang‐Bo; Yang, Guo‐Xun; Hu, Jin‐Feng
Abstract: Twelve new ent‐abietane diterpenoids, chlorabietins A—L, are isolated and fully characterized.